Martabat Kemanusiaan Dalam Al Quran Menurut Tafsir Al Azhar Karya Prof Hamka - Kurniawan, Sandriya; Pulungan, Juli Julaiha (Universitas Cokroaminoto Yogyakarta, 2026)
This study of the concept of human dignity in the Qur'an focuses on Prof. Hamka's interpretation in the Tafsir Al-Azhar. With thematic interpretation (tafsīr maudhū‘ī) it reveals how the Qur'an interprets human dignity as a divine gift as well as a moral mandate that demands ethical and social responsibility, especially in; QS. Al-Isrā’ [17]:70, QS. Al-Baqarah [2]:30, QS. At-Tīn [95]:4–5, QS. An-Nisā’ [4]:1, and QS. Al-Ḥujurāt [49]:13. The study found four main pillars of human dignity, namely divine creation, the mandate of the caliphate, equal social relations, and spiritual responsibility. The Al-Azhar Tafsir demonstrates contextual and progressive hermeneutic courage, making the Qur'an a guide to life that rejects all forms of discrimination and dehumanization. By integrating classical and modern interpretations, this study confirms that Islam offers a paradigm of human dignity that is in line with universal values ​​of justice and is relevant to responding to global humanitarian issues.